DEVELOPMENT OF THEMATIC HANDOUT MATERIALS BASED ON THE LOCAL WISDOM OF NUTMEG FOR LEARNING - Raharti, Nelli; Jarmita, Nida; Hayati, Zikra; Ramadhani, Desi (Jurnal Ilmiah Didaktika, 2024)
Their perception causes a lack of student interest in learning through printed teaching materials that local wisdom presented in textbooks is not relevant to the local knowledge of their region. In addition, most teachers do not utilize locally-based teaching materials, reducing student involvement in the learning process. This study aimed to develop and assess the feasibility of thematic teaching materials based on local wisdom, evaluate the feasibility of the teaching materials, and Assess teacher responses to the teaching materials. The research method used was Research and Development (R&D) using the ADDIE model, including the stages of analysis, design, development, implementation, and evaluation. During the analysis phase, a needs assessment was carried out to ensure the relevance of local wisdom, especially regarding the material on nutmeg, in the teaching materials. The study subjects were grade IV students of MIN 2 South Aceh. The research instruments included a validation questionnaire from media and material experts and a response questionnaire from teachers and students. The validation results showed that local wisdom-based teaching materials about nutmeg and its benefits were considered feasible, with a score of 75% from media experts and 73% from material experts, categorized as "feasible." Students' responses to the teaching materials showed that the materials were very interesting, with a score of 94.5%, while teachers' responses reached 72%, categorized as "interesting." The implications of this study indicate that the development of locally based teaching materials can significantly increase students' interest and involvement in learning and provide practical guidance for teachers in utilizing materials relevant to the local context.